Using Multimedia in Business Communication Learning: Case studies to Improve Vocational Students Business Presentations. - Nurdin Hidayat; Suroto Suroto (AL-ISHLAH: Jurnal Pendidikan, 2023)
Unemployment in Indonesia is more dominated by SMK graduates compared to other graduates. This phenomenon indicates that learning at SMK must be improved immediately. This study aims to provide an overview of multimedia learning enhancing vocational students' business presentation competence. This research focuses on knowing the differences in business presentation competencies between Vocational School students majoring in marketing who use multimedia-based digital touch. This study used a quasi-experimental design. This study's population was class X students majoring in Vocational School marketing in Bandar Lampung with a sample. The experimental class was class X PM 1 SMK PGRI Bandar Lampung while the control class was class X PM 1 SMK Negeri 7 Bandar Lampung. This study revealed significant differences in business presentation competencies between the experimental and control groups. The use of multimedia learning can improve the competence of business presentations.